The synthesis of novel crown ethers Part.I,Coumarin Derivatives of Crown Ethers,(#) - (:unkn) unknown (My University, 1992)
, The synthesis and structural characterisation of coumarin derivatives of some macrocyclic ethers was reported. They were obtained from 1,2,3-trihydroxy and 1,2,4-trihydroxyphenols by reacting with ketoesters. The reaction of dihydroxy coumarins with dichlorides of polyglycols in potassium carbonate /DMF/ water afforded the crown ethers in good yields. © 1992, Taylor & Francis Group, LLC. All rights reserved.